Perilaku Caring Perawat dalam Penerapan Komunikasi Terapeutik di Rumah Sakit X Provinsi Sulawesi Selatan - Syamsuddin, Syamsuddin (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
Caring behavior of nurses in implementing therapeutic communication in hospital X, South Sulawesi aims a) to determine the process of caring behavior of nurses in therapeutic communication and interaction seen from pre nurse orientation effects on the client and the nurse caring behavior seen in Therapeutic communication interaction and orientation of the pre-nursing on the client in the Hospital X South Sulawesi. The results showed that a) the application of the caring behavior of nurses with a current client application on therapeutic communication in pre interaction section, the nurses must prepare before meeting with clients such as reading the report books of client, hen introductory phase or orientation. The orientation phase is an early stage start interacting with clients at the start with regards to the client's condition and asking non-verbal and verbal language greetings terminated. b) While the effects of nurse caring behavior performed by the client when performing therapeutic communication received a positive response from the client or the client's family, because as long as the client is treated with good care so that clients are able to realize self-acceptance because of unnoticed.